Предмет: Алгебра,
автор: meshanyalo
Помогите
Примените формулу сокращённого умножения
(x-2)^2
x^4+4x^2+4
2(x^4-16)
Ответы
Автор ответа:
0
1) (x - 2)² = x² - 2 * x * 2 + 2² = x² - 4x + 4
2) x⁴ + 4x² + 4 = (x²)² + 2 * 2 * x² + 2² = (x² + 2)²
3) 2(x⁴ - 16) = 2[(x²)² - 4²] = 2(x² - 4)(x² + 4) = 2(x - 2)(x + 2)(x² + 4)
Похожие вопросы
Предмет: Информатика,
автор: taniaustinova013
Предмет: Информатика,
автор: maxpapimu
Предмет: Английский язык,
автор: Niggggggggaaa
Предмет: История,
автор: ssona5362
Предмет: Математика,
автор: Julia5ju